Hospital clusters of invasive Group B Streptococcal disease: a systematic review - Collin,SM; Lamb,P; Jauneikaite,E; Le,Doare K; Creti,R; Berardi,A; Heath,PT; Sriskandan,S; Lamagni,T (Journal of Infection, 2019)
Objectives: To characterize outbreaks of invasive Group B Streptococcal (iGBS) disease in hospitals.Methods: Systematic review using electronic databases to identify studies describing iGBS outbreaks/clusters or cross-infection/acquisition in healthcare settings where ‘cluster’ was defined as ≥2 linked cases. PROSPERO CRD42018096297.Results: Twenty-five references were included describing 30 hospital clusters (26 neonatal, 4 adult) in 11 countries from 1966 to 2019. Cross-infection between unrelated neonates was reported in 19 clusters involving an early-onset (<7 days of life; n=3), late-onset (7–90 days; n=13) index case or colonized infant (n=3) followed by one or more late-onset cases (median serial interval 9 days (IQR 3–17, range 0–50 days, n=45)); linkage was determined by phage typing in 3 clusters, PFGE/MLST/PCR in 8, WGS in 4, non-molecular methods in 4. Postulated routes of transmission in neonatal clusters were via clinical personnel and equipment, particularly during periods of crowding and high patient-to-nurse ratio. Of 4 adult clusters, one was attributed to droplet spread between respiratory cases, one to handling of haemodialysis catheters and two unspecified.Conclusions: Long intervals between cases were identified in most of the clusters, a characteristic which potentially hinders detection of GBS hospital outbreaks without enhanced surveillance supported by genomics.